The Outcome of Post-cardiotomy Extracorporeal Membrane Oxygenation in Neonates and Pediatric Patients: A Systematic Review and Meta-Analysis - Cho, Hwa Jin; Choi, Insu; Kwak, Yujin; Kim, Do Wan; Habimana, Reverien; Jeong, In-Seok (Frontiers in Pediatrics, 2022)
Objective: Post-cardiotomy extracorporeal membrane oxygenation (PC-ECMO) is a known rescue therapy for neonates and pediatric patients who failed to wean from cardiopulmonary bypass (CPB) or who deteriorate in intensive care unit (ICU) due to various reasons such as low cardiac output syndrome (LCOS), cardiac arrest and respiratory failure. We conducted a systematic review and meta-analysis to assess the survival in neonates and pediatric patients who require PC-ECMO and sought the difference in survivals by each indication for PC-ECMO. Design: Systematic review and meta-analysis Setting: Multi-institutional analysis Participants: Neonates and pediatric patients who requires PC- ECMO. Interventions: ECMO after open-heart surgery. Results: Twenty-six studies were included in the analysis with a total of 186,648 patients and the proportion of the population who underwent PC-ECMO was 2.5% (2,683 patients). The overall pooled proportion of survival in this population was 43.3% (95% Confidence interval (CI): 41.3 - 45.3%; I2:1%). The survival by indications of PC-ECMO were 44.6% (95% CI: 42.6 - 46.6; I2:0%) for CPB weaning failure, 47.3% (95% CI: 39.9-54.7%; I2: 5%) for LCOS, 37.6% (95% CI: 31.0-44.3%; I2: 32%) for cardiac arrest and 47.7% (95% CI: 32.5-63.1%; I2: 0%) for respiratory failure. Survival from PC-ECMO for single ventricle or biventricular physiology, was reported by 12 studies. The risk ratio (RR) was 0.74 for survival in patients with single ventricle physiology. (95% CI: 0.63-0.86; I2: 40%, P < 0.001) Eight studies reported on the survival after PC-ECMO for genetic conditions. The RR was 0.93 for survival in patients with genetic condition (95% CI: 0.52 – 1.65; I2: 65%, P = 0.812). Conclusions: PC-ECMO is an effective modality to support neonates and pediatric patients in case of failed CPB weaning and deterioration in ICU. Even though ECMO seems to improve survival, mortality and morbidity remain high, especially in neonates and pediatric patients with single ventricle physiology. Most genetic conditions alone should not be considered a contraindication to ECMO support, further studies are needed to determine which genetic abnormalities are associated with favorable outcome.